Exploring the Dynamics of Enzyme Activity: Environmental and Biological Influences - Akram, Muhammad; Rehman, Urooj; Ahmed, Misbah; Umaru, Isaac John (African Journal of Biochemistry and Molecular Biology Research, 2025)
The work presents the classification of enzymes and factors that are affecting enzymatic reactions in the living systems. Factors such as temperature, pH, enzyme concentration, substrate concentration, factors of inhibition, factors of activation, and incubation time are important in influencing enzyme reactions, which are responsible for controlling components in living systems. The majority of enzymes are three-dimensional molecules with complex molecular networks and sensitive to various environmental factors.